Trends in Location of Death in Patients With Aortic Aneurysm and Dissection. (August 2022) - DeCicco, Danielle; Dimachkie, Ziad O.; Khan, Muhammad Z.; Khan, Muhammad S.; Khan, Muhammad U.; Khan, Safi U.
Aortic dissections and aneurysms (ADA) are associated with significant morbidity and mortality, and location of death for these patients is important in determining impact on end of life care. We analyzed the Centers for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research database. Black and Hispanic backgrounds had decreased odds of dying at home from ADA. Married or educated individuals tended to die at home at a higher rate than unmarried individuals. Overall, we have shown place of death in individuals with ADA is different among individuals of different demographics.